(untitled) (Journal of Entrepreneurship and Business, 2025)
This study analysed the market positioning for new product launch to achieve market viable product (MVP) which is a mini-launch of the CocoGlow Milk Drink. A sample of three hundred young and old adults between 18 and 55 years old was taken for this study. Data were obtained through questionnaire administration to individuals residing in five Local Government Areas (LGAs) in Lagos state. Out of the three hundred (300) samples, 250 copies of the questionnaire were filled and returned. However, 8 copies were not properly filled and were therefore excluded from the analysis. In all, 242 copies of the questionnaire were validly filled and used for the data analysis. It was found that substantial portion of the respondents is aware of the benefits of consuming CocoGlow Milk Drink. The study also revealed in the survey, 93% of the respondents have interest in drinking CocoGlow Milk Drink. The results also showed that 32.6% of the respondents are willing to become distributors of CocoGlow Milk Drink. It is recommended that Facebook, Instagram, SMS and Whatsapp should be mainly used as they are the most preferred channels by majority of the respondents.